LA SUBSTITUTION DE LA CAFEICULTURE PAR L’ELAEICULTURE POUR LA RELANCE DE L’ECONOMIE DU HAUT-UELE EN REPUBLIQUE DEMOCRATIQUE DU CONGO - SHINDANO, Jean-Claude; DANGA ANZIBONDEYI, (IJRDO-Journal of Applied Science, 2019)
After the fall of coffee, the palm oil took over the province of Haut-Uele in the agricultural domain. With the importance that the local habitants have put in the palm oil and the possibility of having development from this product, this study wants to verify if palm oil instead of coffee presents an opportunity for an economic comeback of this province.After the analysis, the cultivation of palm for oil production revealed itself profitable than that of coffee production for the progress of the province of Haut-Uele